Design and Analysis of Microstrip Photonic Band Gap Filter for Suppression of Periodicity - Baral , R. N.; Singhal, P. K. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A design for a microstrip band reject filter is presented in this paper. The proposed filter is compact in structure and provides an accurate band gap. Optimized length is applied to photonic band gap (PBG) structures etched in the ground plane for suppressing periodicity in the frequency response. Detailed analysis of the frequency response of the conventional microstrip filter along with the PBG filter has been carried out in this paper.